Fundamentos da objetividade na produção discursiva - Amaral, Gustavo Rick (2009)
The aim of this study is to make a contribution towards the development of a Peircean approach to some questions in the communication theories, namely, the category of objectivity that directs the discursive media production. For this purpose, the category was divided into two key-concepts that sustain it: reality and information . For each one of these two key concepts, we dedicated two specific chapters. The first part (chapter 1 and 2) focuses on the definition of science presented by Peirce in his works to prepare the ground for the discussion with some constructivists (in sociology and biology). Their theoretical interpretations were analyzed against the background of the controversy about the universals . It is argued that, with the realism of Peirce, we can only conceive of a unique and evolutionary reality instead of multiple realities (as defended by many constructivists). In the second part (chapter 3 and 4), in order to sustain the hypothesis of a unique and evolutionary reality , a non-exhaustive analysis of the Peircean concept of information is carried out . The claim is sustained that it can be understood as a means to bring into communication various independent worlds that may constitute the reality (as a whole). Since the present study is a predominantly reflexive inquiry, an argumentativedeductive method is used based on confrontation of theories and ideas with the purpose of arriving at coherent conclusions. From the ontological perspective conceiving the concept of communication and information, the synechistic approach to the concept of reality can play an important role in the communication theories (as well as in some others theoretical reflexions on the media practices). According to these premises, there is a long and continuous informational process that gives a proper reality and a certain objectivity to signs